Electric birefringence of carbon nanotubes: Single- vs double-walled. (January 2018) - Arenas-Guerrero, Paloma; Jiménez, María L.; Scott, Kenneth; Donovan, Kevin J.
Abstract: When subjected to an external electric field, carbon nanotubes in suspension are polarized and forced to rotate due to the consequent electric torque. The analysis of this electro-orientation is interesting not only at a fundamental level, but also because of the many applications that require the alignment of these particles. Moreover, the study of the interaction of the tubes with an electric field is a highly informative non-invasive technique, able to provide much information on their microscopic properties. In order to monitor the orientation of the particles, in this work we measured the macroscopic optical anisotropy of the suspension, or electric birefringence, that emerges when the tubes are oriented by the field. Two types of particle were studied: single-walled and double-walled carbon nanotubes. The electric, optical and geometrical properties of the suspended tubes were analysed via the field dependence of the electric birefringence over a wide range. Remarkably, it was found that, whilst single-walled carbon nanotubes show a positive signal, double-walled carbon nanotubes exhibit a negative birefringence caused by an anomalous optical anisotropy. Graphical abstract: Image 1